Post-Soviet Koreans - Fumagalli, Matteo (Oxford University Press, 2022)
Korean communities have lived in the territory of the Russian Empire, the Soviet Union and successor states for over 150 years. The history of the post-Soviet Koreans has been shaped by multiple transnational mobilities, including a dispersal across a wide territory. As of 2021 two thirds of approximately half a million post-Soviet Koreans are settled in Central Asia, primarily in Kazakhstan and Uzbekistan: one third is in Russia; and a growing community of several tens of thousands is working and residing in South Korea. The ethnonym subsumes three distinct sets of sub-ethnic communities. The largest group includes the Koryo Saram, i.e., the descendants of those who migrated from the northern part of the Korean peninsula to the Russian Empire from the second half of the 19th century onwards. Most were deported to Central Asia in 1937. The second, much smaller group includes the Sakhalin Koreans. Originally from the southern part of the Korean Peninsula, they had migrated to the southern part of Sakhalin Island (then under Japanese colonial rule) between 1939 and 1945. In addition, between 1946 and 1949 some students and contract workers from North Korea decided to remain on Soviet territory instead of returning to their country of origin. Despite some commonalities across these groups, the notion of Soviet/post-Soviet Koreans bundles together peoples of different origins, patterns of settlement, identities and even links to the Korean Peninsula. The collapse of the Soviet Union and greater engagement by South Korea in the following decades ushered in an era of significant challenges and opportunities for the post-Soviet Koreans. It also brought about new mobilities and revealed growing inter-generational differences in terms of language and broader cultural loss, maintenance or erosion of group boundaries and degrees of integration into local societies. Traditionally, scholarship has focused on the 1937 deportations, the different historical geographies of the group, and evolving conceptions of home and ...